Frequency of pulp canal obliteration in primary teeth after traumatic dental injury and its association with related variables - Samantha Alves do Nascimento MOURA; Keilla Couto MACHADO; Michele Machado LENZI; Marcia Rejane Thomas Canabarro ANDRADE; Mirian de Waele Souchois de MARSILLAC; Vera CAMPOS (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Objective The aim of this study was to determine the frequency of pulp canal obliteration (PCO) after traumatic dental injury (TDI) of primary anterior teeth and to investigate its relation with the related variables. Methods This retrospective study has been done with dental records of patients selected from the Paediatric Dental Trauma Clinic between 2006 and 2016. Those who had PCO in the primary anterior teeth and were aged 0-108 months at the time of trauma were considered eligible. Data related to patients and TDI, such as sex, the child's age at the time of trauma, aetiology, affected teeth, the child's age at the time of the eruption of the permanent successor as well as the presence of crown discoloration were extracted from the dental records. Results Among the 483 children with traumatised teeth, 14.9% had PCO and the most of them exhibited crown discoloration. The average age of the children at the time of the trauma was 38 months and the most common aetiology of the TDI was falls. The average time for the beginning of the PCO process was 13.5 months. There was no statistically significant association between the child's age at the time of trauma and the types of TDI, PCO and the presence of crown discoloration. Conclusions The frequency of PCO was relatively low though the presence of crown discoloration was considerable. There was no association between the child's age at the time of trauma and the studied variable.